2021
DOI: 10.1038/s41467-021-21718-y
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus induces an itaconate-dominated immunometabolic response that drives biofilm formation

Abstract: Staphylococcus aureus is a prominent human pathogen that readily adapts to host immune defenses. Here, we show that, in contrast to Gram-negative pathogens, S. aureus induces a distinct airway immunometabolic response dominated by the release of the electrophilic metabolite, itaconate. The itaconate synthetic enzyme, IRG1, is activated by host mitochondrial stress, which is induced by staphylococcal glycolysis. Itaconate inhibits S. aureus glycolysis and selects for strains that re-direct carbon flux to fuel e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 54 publications
2
76
0
Order By: Relevance
“…Tomlinson et al investigated the immunometabolic response of S. aureus [137]. Their data showed that S. aureus induced the production of the immunoregulatory metabolite itaconate in airway immune cells by stimulating mitochondrial oxidative stress.…”
Section: Biofilm Formation-an Adaptive Mechanism Of S Aureus In Cystic Fibrosismentioning
confidence: 99%
“…Tomlinson et al investigated the immunometabolic response of S. aureus [137]. Their data showed that S. aureus induced the production of the immunoregulatory metabolite itaconate in airway immune cells by stimulating mitochondrial oxidative stress.…”
Section: Biofilm Formation-an Adaptive Mechanism Of S Aureus In Cystic Fibrosismentioning
confidence: 99%
“…A recent study of the role of itaconate in S. aureus endophthalmitis indicates that TLR2 signaling is not sufficient, as heat-killed S. aureus, lipoteichoic acid, and peptidoglycan do not stimulate IRG1 expression to the same extent as live bacteria (63). Instead, IRG1 expression can be mitigated by administration of a mitochondrial ROS scavenger, suggesting that host mitochondrial stress and/or oxidants promote IRG1 expression during S. aureus infection (56).…”
Section: S Aureus Induces An Itaconate-dominated Immunometabolic Responsementioning
confidence: 99%
“…Mitochondrial ROS production and itaconate accumulation in the murine airway depend on S. aureus glycolysis, demonstrating that bacterial metabolism itself stimulates itaconate generation during S. aureus lung infection (56). The exact mechanism that connects bacterial metabolism to host metabolic reprogramming still needs to be determined.…”
Section: S Aureus Induces An Itaconate-dominated Immunometabolic Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Itaconate is abundantly produced by macrophages and the host airway after infection with P. aeruginosa [21,41]. Itaconate is toxic to many bacterial species, such as Staphylococcus aureus, Mycobacterium tuberculosis and Legionella pneumophila [45][46][47] targeting the activity of both isocitrate lyase (aceA) [48] and aldolase, major metabolic nodes that control the function of the anti-oxidant glyoxylate shunt [49,50] and glycolysis, respectively (Figure 2). However, several important airway pathogens, including P. aeruginosa, M. tuberculosis and Aspergillus species can also metabolize itaconate [51].…”
Section: P Aeruginosa Induces and Assimilates Host Itaconate To Cause Long-term Diseasementioning
confidence: 99%